OPTIMIZING THE ROLE OF THE INDONESIAN MARINE CORPS IN ORGANIZING COASTAL DEFENSE OPERATIONS - Taufik Ramdhan; Juang Pawana; Kukuh Setyo Pambudi (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT This study aims to analyze the marine corps to play a bigger role in coastal defense operations in Indonesia. Based on Presidential Regulation Number 66 of 2019, article 63 states that the Marine corps is designated as the Main Operations Command. This provision has implications for the Marines to carry out several operations under the direct command of the TNI Commander. Some of the operations that can be carried out include amphibious operations, coastal defense operations, and securing strategic outer islands within OMP and OMSP. In particular, coastal defense operations are essential operations that the Marine Corps will be able to carry out properly because the coastal defense is one of its primary capabilities. The Marine Corps as the central coordinator in Coastal Defense Operations is also supported by article 153 which states the authority of the Marine Corps as the Main Guidance Command in fostering Marine unit elements and maritime potential in the region. Thus, it becomes a necessity if the Marine Corps becomes the main driving force for the implementation of Coastal Defense Operations along with the frontier coastal areas in Indonesia. This study used a qualitative descriptive analysis approach with the primary data source obtained from a literature review. It is hoped that the results of this study can contribute to the Republic of Indonesia in considering the Marine Corps to be able to play an active role by starting to develop the Composite Marine Unit organization. Then it will be more optimal if the Composite Marine Unit is dislocated throughout the Indonesian homeland, especially in areas that have the Main Base of the Indonesian Navy as the central role in the implementation of the current Coastal Defense Operations. Keywords: Optimizing ,Marine, Coastal Defense Operations.